Preparation method of two-dimensional Ti3C2-yNyTx MXene powder with adjustable N content

The Ti3AlC2-yNy MAX phase precursor is synthesized through the normal pressure sintering method, and the high-purity two-dimensional Ti3C2-yNyTx MXene material is prepared using a low-concentration HF solution etching method, which solves the problems of low preparation efficiency and difficult performance control in the existing technology. problem, achieving efficient preparation of materials and precise control of properties.

CN119330316APending Publication Date: 2025-01-21BEIJING JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410981469.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

It is difficult to prepare two-dimensional Ti3C2-yNyTx MXene materials with high purity and adjustable N content in the prior art, and traditional preparation methods have problems such as the use of high-concentration HF solutions and long-term etching, which limits the large-scale production and performance regulation of materials.

Method used

The Ti3AlC2-yNy MAX phase precursor powder is synthesized using the normal pressure sintering method, and a 20% concentration HF solution is used for magnetic stirring etching in a 40-60°C water bath environment. It only takes 0.5 hours to prepare high-purity dielectric. Dimensional Ti3C2-yNyTx MXene material.

Benefits of technology

It significantly improves the preparation efficiency, shortens the preparation time, reduces the production cost, and achieves precise control of conductivity, electrochemical activity, wave absorption, catalysis and other properties by adjusting the N content, broadening the application field of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330316A_ABST
    Figure CN119330316A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of two-dimensional Ti < 3 > C < 2-y > N < y > T < x > MXene powder with adjustable N content. Yt; Yt; and 2, the preparation method belongs to the field of preparation of MXene nanometer materials. The preparation method comprises the following two processes: firstly, taking Ti powder, AlN powder, Al powder and C powder as raw material powder, mixing the raw material powder according to a certain proportion, and carrying out a normal pressure sintering process in an Ar atmosphere at the temperature of 1400-1500 DEG C for 1-3 hours to obtain high-purity Ti3AlC2-yNy MAX phase precursor powder with adjustable N content; and then adding the Ti3AlC2-yNy powder into a 20% HF solution, heating in a water bath at the temperature of 40-60 DEG C and magnetically stirring at the speed of 300 r / min to promote the reaction, and successfully synthesizing the two-dimensional Ti3C2-yNyTx MXene with adjustable N content. According to the preparation method disclosed by the invention, the high-purity Ti < 3 > Al < 2-y > N < y > MAX phase and Ti < 3 > C < 2-y > N < y > T < x > MXene powder with adjustable N content are prepared, the MAX phase and MXene family members are enriched, and higher application potential is shown; and the preparation time of the current carbonitride MXene is shortened from dozens of hours or even dozens of hours to 0.5 hour, so that the preparation efficiency is remarkably improved, and the research and development cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation of MXene nanomaterials, and specifically relates to a two-dimensional Ti3C 2- y N y T x Preparation method of MXene powder. Background Art

[0002] MXene is a nanomaterial with a unique two-dimensional layered structure. Since its discovery in 2011, it has become a research hotspot in many fields such as energy, catalysis, environmental protection, electromagnetic wave absorption and shielding. The chemical formula of MXene is usually expressed as M n+ 1X n T x (n = 1, 2 or 3), where M represents a transition metal (such as tungsten, molybdenum, niobium, chromium, titanium, etc.), X is carbon or nitrogen, T x It represents the surface functional group (such as -OH, -F or -Cl, etc.). MXene is usually obtained by chemically etching away the A-site element from a MAX phase precursor (where A is a third- or fourth-group element) to obtain a two-dimensional MXene.

[0003] The most studied MXene family is Ti3C2T x , because it exhibits many unique physical and chemical properties. x The introduction of N into Ti3C2T will change its electronic structure, chemical properties and surface activity because N has a higher electronegativity than C. x Plasma nitriding treatment significantly improves the x However, this technology can only make the N content reach 4.0at.% (atomic ratio). If the N content is increased by prolonging the nitriding time, it will destroy the Ti3C2T x Structure (Reference 1, ACS Appl. Mater. Interfaces 2021, 13(41): 49242). The Ti3AlCN MAX phase precursor powder was obtained by solid solution method, and then the two-dimensional Ti3CNT was obtained by chemical etching. x MXene not only increases the N content, but also Ti3CNT x Some properties are significantly better than Ti3C2T x (Reference 2, ACS Appl. Nano Mater. 2022, 5: 17133). Inspired by the above results, if a two-dimensional Ti3C with adjustable N content can be obtained 2-y N y T x(0 < y < 2) MXene, whose properties can also be precisely adjusted to meet the requirements of functional materials in different fields. However, to date, there has been a lack of relevant reports on two-dimensional Ti3C 2-y N y T x MXene, probably because it is difficult to prepare high-purity Ti3AlC 2-y N y (0 < y < 2) MAX-phase precursor powder. Therefore, preparing high-purity Ti3AlC 2-y N y precursor powder is a key problem that must be solved.

[0004] Currently, two-dimensional Ti3CNT can usually be obtained by etching Ti3AlCN with a high-concentration HF solution for a long time. x Literature 3 (Nanomicro Lett. 2021, 13(1): 63) reported that after etching Ti3AlCN powder with 40% HF solution at room temperature for 48 hours, Ti3CNT x was obtained. Literature 4 (Environ. Res. 2022, 205: 112532) reported that after etching Ti3AlCN powder with 48% HF solution at room temperature for 24 hours, Ti3CNT x was obtained. Literature 5 (J Alloys Compd 2023, 952, 170043) reported that after etching Ti3AlCN powder with 30% HF solution at 35 °C for 18 hours, Ti3CNT x was obtained. In addition, even if the relatively safe molten salt method is used to etch the precursor Ti3AlCN to prepare Ti3CNT x , the etching time still needs to be as long as 24 hours. Literature 6 (Nat. Mater. 2020, 19(8): 894) reported that after etching Ti3AlCN powder with CuCl2 molten salt at 700 °C for 24 hours, Ti3CNT x was obtained, but it only contains Cl- surface functional groups. The high-concentration acid solution increases the danger to operators during the preparation process, and the high-temperature molten salt method also increases energy consumption. Especially, the long-time etching limits the large-scale production of Ti3CNT x .

[0005] The present invention prepares high-purity Ti3AlC with adjustable N content 2-y N y MAX-phase precursor powder. By etching it with a relatively low-concentration 20% HF solution and with the promotion of a water bath temperature of 40 - 60 °C and magnetic stirring, two-dimensional Ti3C with adjustable N content 2-y N y T xMXene products. In particular, the present invention converts Ti3C 2-y N y T x The preparation time of MXene is shortened from more than ten hours to 0.5 hours, which significantly improves the preparation efficiency. 2-y N y T x MXene can achieve precise control of conductivity, electrochemical activity, wave absorption, catalysis and other properties by adjusting the N content, which will greatly broaden its application areas. Summary of the invention

[0006] The present invention provides a Ti3AlC with adjustable N content. 2-y N y MAX phase precursor powder and two-dimensional Ti3C 2-y N y T x Preparation method of MXene powder. The present invention uses the common pressure sintering method in industry to synthesize Ti3AlC 2-y N y MAX phase precursor powder, and then use 20% concentration HF solution as an etchant to etch Ti3AlC 2-y N y The precursor powder was etched, and the reaction was promoted by water bath heating (40-60°C) and magnetic stirring (300 rpm). Two-dimensional Ti3C was prepared in just 0.5 hours. 2-y N y T x MXene. The present invention not only enriches the MAX phase and MXene family members, but also significantly improves the preparation efficiency, showing the potential for large-scale production and application.

[0007] A two-dimensional Ti3C with adjustable nitrogen content 2-y N y T x The preparation method of MXene powder includes the following specific steps:

[0008] (1) Step 1: Preparation of Ti3AlC precursor with adjustable N content 2-y N y MAX phase powder

[0009] (a) The formula of raw material powder is as follows: Ti:AlN:Al:C=3:y:(1.1-y):(2-y), 0 <y<2

[0010] (b) After the raw material powder is mixed evenly in a certain proportion, the normal pressure sintering process is adopted: 1400-1500℃, heat preservation for 1-3 hours, and then the

[0011] Cool to room temperature. The whole process is carried out in an Ar gas protection atmosphere.

[0012] (c) Crush the obtained sample and sieve it through a 200-mesh sieve to obtain the precursor Ti3AlC 2-y N y powder

[0013] (2) Step Two: Prepare two-dimensional Ti3C with adjustable N content 2-y N y T x MXene powder

[0014] (a) Take 10 - 40 ml of 20% HF solution and drop it into a conical flask. Slowly add 0.5 - 10 grams of Ti3AlC 2-y N y powder, and the reaction is carried out in

[0015] a 40 - 60°C water bath environment with magnetic stirring (300 revolutions per minute). The reaction time is 0.5 - 4 hours.

[0016] (b) Pour the corrosion product after the reaction into a centrifuge tube, and centrifuge and wash it successively with deionized water and absolute ethanol until the

[0017] pH value of the supernatant is about 7.

[0018] (c) Put the obtained black slurry-like product into a vacuum drying oven and dry it under vacuum at 60°C to obtain the corresponding powder Ti3C 2-y N y T x powder.

[0019] The beneficial effects of the present invention are as follows:

[0020] (1) For the Ti3AlC 2-y N y MAX phase and Ti3C 2-y N y T x prepared by the present invention, the N element at the X site is continuous and adjustable within the range of 0 < y ≤ 1.1, which will greatly enrich the members of the MAX and MXene families and provide guiding significance for the research and development of advanced materials.

[0021] (2) By optimizing the preparation conditions, the present invention reduces the volume concentration of the HF solution to 20% and the reaction time to 0.5 hours,

[0022] reduces the production cost, improves the preparation efficiency, and reduces the harm to the operator and the environment to a certain extent.

[0023] (3) High-purity Ti3AlC prepared by the present invention 2-y N y MAX phase and Ti3C 2-y N y T x MXene can flexibly adjust its electronic and chemical properties by adjusting the N content to meet the different needs of specific fields.

[0024] (4) Since most MXene can be obtained by etching the precursor MAX phase, the present invention can also be applied to the preparation of MXene powders of other systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The Ti3AlC prepared in the first embodiment of the present invention 1.7 N 0.3 MAX phase precursor and Ti3C 1.7 N 0.3 T x X-ray diffraction (XRD) pattern of MXene powder.

[0026] Figure 2 (a) is the Ti3AlC synthesized in the first embodiment of the present invention 1.7 N 0.3 Scanning electron microscope (SEM) image of MAX phase precursor powder. Figure 2 (b) is the Ti3C synthesized by etching for 0.5 hours in embodiment 1 1.7 N 0.3 T x SEM image of MXene powder. Figure 3 The Ti3CNT synthesized by etching for 4 hours in the fifth embodiment of the present invention x SEM image of MXene powder. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments. The embodiments listed below are part of the embodiments of the present invention, but not all. These examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Under the condition that there is no substantial change in the technical content, they can also be regarded as the scope of the present invention.

[0028] Implementation method 1:

[0029] 1. Step 1: Preparation of Ti3AlC 1.7 N 0.3 (y=0.3)MAX phase precursor powder, the steps are as follows:

[0030] (1) The formula of raw material powder is Ti:AlN:Al:C=3:0.3:0.8:1.7

[0031] (2) Mixing: The raw material powder is weighed according to the above-mentioned proportion of ingredients, and the weighed raw material powder and agate balls are sealed in a plastic ball mill at a mass ratio of 1:2, and mixed in a drum ball mill for 24 hours.

[0032] (3) The uniformly mixed raw material powder is taken out and pressed into a green body with a diameter of 50 mm, which is supported by a graphite mold coated with BN.

[0033] (4) The mold is placed in a vacuum atmosphere furnace and a pressureless sintering process is used. The temperature is raised to 1500°C at a rate of 15°C / min, kept at this temperature for 1 hour, and cooled to room temperature with the furnace. The entire process is carried out in an Ar gas protective atmosphere.

[0034] (5) The obtained sample was crushed and passed through a 200-mesh sieve to obtain Ti3AlC 1.7 N 0.3 Precursor powder.

[0035] The prepared Ti3AlC 1.7 N 0.3 The X-ray diffraction (XRD) pattern of the powder is shown in Figure 1 It can be observed that Ti3AlC 1.7 N 0.3 The diffraction peaks of the powder are sharp and clear, reflecting the good crystallinity of the sample. The diffraction peaks at different positions correspond to different crystal planes, such as the diffraction peak at 9.37° corresponds to the (002) crystal plane, the diffraction peak at 18.99° corresponds to the (004) crystal plane, and the diffraction peak at 38.88° corresponds to the (104) crystal plane. 1.7 N 0.3 The scanning electron microscope (SEM) image of the powder is shown in Figure 2 (a), Ti3AlC 1.7 N 0.3 The powder particles show typical MAX phase lamellar characteristics.

[0036] 2. Step 2: Preparation of two-dimensional Ti3C 1.7 N 0.3 T x MXene powder

[0037] (1) Take 10 ml of 20% HF solution and drop it into a conical flask. Slowly add 0.5 g of Ti3AlC 1.7 N 0.3 The reaction was carried out in a 50°C water bath with magnetic stirring (300 rpm) for 0.5 h.

[0038] (2) After the reaction is completed, the corrosion products are poured into a centrifuge tube and washed by centrifugation with deionized water and anhydrous ethanol until the pH value of the supernatant is about 7.

[0039] (3) The obtained black slurry product was placed in a vacuum drying oven and dried under vacuum conditions at 60°C to obtain Ti3C 1.7 N 0.3 T x MXene powder.

[0040] The prepared Ti3C 1.7 N 0.3 T x XRD spectrum of MXene powder is shown in Figure 1 It can be observed that its diffraction peak is relatively 1.7 N 0.3 There are obvious changes, such as the disappearance of the (104) crystal plane diffraction peak at 38.88°, and the shift of the (002) crystal plane diffraction peak to a lower angle of 6.38°. These phenomena indicate that the Al layer in the precursor has been selectively etched away to generate Ti3C 1.7 N 0.3 T x The prepared Ti3C 1.7 N 0.3 T x SEM images of MXene powders are shown in Figure 2 (b), Ti3C 1.7 N 0.3 T x MXene exhibits typical "accordion-like" features.

[0041] Implementation method 2:

[0042] 1. Step 1: Preparation of Ti3AlC 1.5 N 0.5 (y=0.5) MAX phase precursor powder, the steps are as follows:

[0043] (1) The formula of raw material powder is Ti:AlN:Al:C=3:0.5:0.6:1.5

[0044] (2) Mixing: The raw material powder was weighed according to the above-mentioned proportion, and the weighed raw material powder and agate balls were sealed in a plastic ball mill at a mass ratio of 1:2, and mixed in a drum ball mill for 24 hours.

[0045] (3) The uniformly mixed raw material powder is taken out and pressed into a green body with a diameter of 50 mm, which is supported by a graphite mold coated with BN.

[0046] (4) The mold is placed in a vacuum atmosphere furnace and a pressureless sintering process is used. The temperature is raised to 1500°C at a rate of 15°C / min, kept at this temperature for 1 hour, and cooled to room temperature with the furnace. The entire process is carried out in an Ar gas protective atmosphere.

[0047] (5) The obtained sample was crushed and passed through a 200-mesh sieve to obtain the precursor Ti3AlC 1.5 N 0.5 of powder.

[0048] 2. Step 2: Preparation of two-dimensional Ti3C 1.5 N 0.5 T x MXene powder

[0049] (1) Take 10 ml of 20% HF solution and drop it into a conical flask. Slowly add 0.5 g of Ti3AlC 1.5 N 0.5 The reaction was carried out in a 50°C water bath with magnetic stirring (300 rpm) for 0.5 h.

[0050] (2) After the reaction is completed, the corrosion products are poured into a centrifuge tube and washed by centrifugation with deionized water and anhydrous ethanol until the pH value of the supernatant is about 7.

[0051] (3) The obtained black slurry product was placed in a vacuum drying oven and dried under vacuum conditions at 60°C to obtain Ti3C 1.5 N 0.5 T x MXene powder.

[0052] The prepared Ti3C 1.5 N 0.5 T x The microscopic morphology of MXene powder particles under a scanning electron microscope is a typical "accordion shape"

[0053] Features, and the Ti3C obtained in the first embodiment 1.7 N 0.3 T x The MXene microstructure is the same.

[0054] Implementation method three:

[0055] 1. Step 1: Preparation of Ti3AlC 1.2 N 0.8 (y=0.8)MAX phase precursor powder, the steps are as follows:

[0056] (1) The formula of raw material powder is Ti:AlN:Al:C=3:0.8:0.3:1.2

[0057] (2) Mixing: The raw material powder was weighed according to the above-mentioned proportion, and the weighed raw material powder and agate balls were sealed in a plastic ball mill at a mass ratio of 1:2, and mixed in a drum ball mill for 24 hours.

[0058] (3) The uniformly mixed raw material powder is taken out and pressed into a green body with a diameter of 50 mm, which is supported by a graphite mold coated with BN.

[0059] (4) The mold is placed in a vacuum atmosphere furnace and a pressureless sintering process is used. The temperature is raised to 1500°C at a rate of 15°C / min, kept at this temperature for 1 hour, and cooled to room temperature with the furnace. The entire process is carried out in an Ar gas protective atmosphere.

[0060] (5) The obtained sample was crushed and passed through a 200-mesh sieve to obtain the precursor Ti3AlC 1.2 N 0.8 of powder.

[0061] 2. Step 2: Preparation of two-dimensional Ti3C 1.2 N 0.8 T x MXene powder

[0062] (1) Take 10 ml of 20% HF solution and drop it into a conical flask. Slowly add 0.5 g of Ti3AlC 1.2 N 0.8 The reaction was carried out in a 50°C water bath with magnetic stirring (300 rpm) for 0.5 h.

[0063] (2) After the reaction is completed, the corrosion products are poured into a centrifuge tube and washed by centrifugation with deionized water and anhydrous ethanol until the pH value of the supernatant is about 7.

[0064] (3) The obtained black slurry product was placed in a vacuum drying oven and dried under vacuum conditions at 60°C to obtain the corresponding powder Ti3C 1.2 N 0.8 T x Powder.

[0065] The prepared Ti3C 1.2 N 0.8 T x The microscopic morphology of MXene powder particles under a scanning electron microscope is a typical "accordion shape"

[0066] Features, and the Ti3C obtained in the first embodiment 1.7 N 0.3 T x The MXene microstructure is the same.

[0067] Implementation method 4:

[0068] 1. Step 1: Prepare Ti3AlCN (y=1) MAX phase precursor powder, the steps are as follows:

[0069] (1) The formula of raw material powder is Ti:AlN:Al:C=3:1:0.1:1

[0070] (2) Mixing: The raw material powder was weighed according to the above-mentioned proportion, and the weighed raw material powder and agate balls were sealed in a plastic ball mill at a mass ratio of 1:2, and mixed in a drum ball mill for 24 hours.

[0071] (3) The uniformly mixed raw material powder is taken out and pressed into a green body with a diameter of 50 mm, which is supported by a graphite mold coated with BN.

[0072] (4) The mold is placed in a vacuum atmosphere furnace and a pressureless sintering process is used. The temperature is raised to 1500°C at a rate of 15°C / min, kept at this temperature for 1 hour, and cooled to room temperature with the furnace. The entire process is carried out in an Ar gas protective atmosphere.

[0073] (5) The obtained sample is crushed and passed through a 200-mesh sieve to obtain the powder of the precursor Ti3AlCN.

[0074] 2. Step 2: Preparation of two-dimensional Ti3CNT x MXene powder

[0075] (1) Take 10 ml of 20% HF solution and drop it into a conical flask, slowly add 0.5 g of Ti3AlCN powder, and cover the lid. The reaction is carried out in a 50°C water bath environment with magnetic stirring (300 rpm) for 0.5 hours.

[0076] (2) After the reaction is completed, the corrosion products are poured into a centrifuge tube and washed by centrifugation with deionized water and anhydrous ethanol until the pH value of the supernatant is about 7.

[0077] (3) The obtained black slurry product was placed in a vacuum drying oven and dried under vacuum conditions at 60°C to obtain the corresponding powder Ti3CNT x Powder.

[0078] The prepared Ti3CNT x The microscopic morphology of MXene powder particles under a scanning electron microscope is a typical "accordion-shaped" feature, which is similar to the Ti3C 1.7 N 0.3 T x The MXene microstructure is the same.

[0079] Implementation method five:

[0080] 1. Step 1: Prepare Ti3AlCN (y=1) MAX phase precursor powder, the steps are as follows:

[0081] (1) The formula of raw material powder is Ti:AlN:Al:C=3:1:0.1:1

[0082] (2) Mixing: The raw material powder was weighed according to the above-mentioned proportion, and the weighed raw material powder and agate balls were sealed in a plastic ball mill at a mass ratio of 1:2, and mixed in a drum ball mill for 24 hours.

[0083] (3) The uniformly mixed raw material powder is taken out and pressed into a green body with a diameter of 50 mm, which is supported by a graphite mold coated with BN.

[0084] (4) The mold is placed in a vacuum atmosphere furnace and a pressureless sintering process is used. The temperature is raised to 1500°C at a rate of 15°C / min, kept at this temperature for 1 hour, and cooled to room temperature with the furnace. The entire process is carried out in an Ar gas protective atmosphere.

[0085] (5) The obtained sample is crushed and passed through a 200-mesh sieve to obtain the powder of the precursor Ti3AlCN.

[0086] 2. Step 2: Preparation of two-dimensional Ti3CNT x MXene powder

[0087] (1) Take 10 ml of 20% HF solution and drop it into a conical flask, slowly add 0.5 g of Ti3AlCN powder, and cover the lid. The reaction is carried out in a 50°C water bath environment with magnetic stirring (300 rpm) for 4 hours.

[0088] (2) After the reaction is completed, the corrosion products are poured into a centrifuge tube and washed by centrifugation with deionized water and anhydrous ethanol until the pH value of the supernatant is about 7.

[0089] (3) The obtained black slurry product was placed in a vacuum drying oven and dried under vacuum conditions at 60°C to obtain the corresponding powder Ti3CNT x Powder.

[0090] The prepared Ti3CNT x SEM images of MXene powders are shown in Figure 3 , Ti3CNT etched for 4 hours x The MXene powder particles still show the typical "accordion-like" characteristics, which is different from the Ti3C obtained by etching for 0.5 hours in embodiments 1 to 4. 2-y N y T x In comparison, no significant changes occurred in the microstructure.

Claims

1. A two-dimensional Ti3C with adjustable N content 2-y N y T x The method for preparing MXene powder is characterized by: (1) Step 1: Preparation of Ti3AlC with adjustable N content 2-y N y MAX phase precursor powder (a) The formula of raw material powder is as follows: Ti:AlN:Al:C=3:y:(1.1-y):(2-y), 0 <y<2 (b) After the raw material powder is evenly mixed, the normal pressure sintering process is adopted: 1400-1500℃, keep warm for 1-3 hours, and cool to room temperature with the furnace. The whole process is carried out in a vacuum Ar gas protective atmosphere (c) The obtained sample was crushed and sieved through a 200-mesh sieve to obtain the precursor Ti3AlC 2-y N y Powder (2) Step 2: Preparation of two-dimensional Ti3C with adjustable N content 2-y N y T x MXene powder (a) Take 10-40 ml of 20 wt.% HF solution and drop it into a conical flask, then slowly add 0.5-10 g of Ti3AlC 2-y N y The powder is reacted in a water bath at 40-60°C with magnetic stirring at 300 rpm for 0.5-4 hours. (b) The corrosion product after the reaction is poured into a centrifuge tube and washed by centrifugation with deionized water and anhydrous ethanol successively until the pH value of the supernatant is about 7. (c) The obtained black slurry product was placed in a vacuum drying oven and dried under vacuum conditions at 60°C to obtain the corresponding powder Ti3C 2-y N y T x Powder.

2. A Ti3C with adjustable N content 2-y N y T x The method for preparing MXene powder is characterized in that: Ti3AlC 2-y N y The preparation process of the MAX phase precursor is: using Ti powder, AlN powder, Al powder and C powder as raw material powders, mixing them in a certain proportion, sintering at normal pressure, and keeping the temperature at 1400-1500° C. for 1-3 hours.

3. A Ti3C with adjustable N content 2-y N y T x The method for preparing MXene powder is characterized in that: Precursor Ti3AlC 2- y N y The preparation of MAX phase powder is not limited to the above-mentioned raw material powder formula.

4. A Ti3C with adjustable N content 2-y N y T x The method for preparing MXene powder is characterized in that: The concentration of the HF solution is not limited to the above concentration.

5. A Ti3C with adjustable N content 2-y N y T x The method for preparing MXene powder is characterized in that: The temperature of water bath heating is not limited to the above-mentioned temperature.

6. A Ti3C with adjustable N content 2-y N y T x The method for preparing MXene powder is characterized in that: The etching time is not limited to the above time.

7. A Ti3C with adjustable N content 2-y N y T x The method for preparing MXene powder is characterized in that: It can be extended to other systems of MAX phase X-position precursor powders and two-dimensional MXene powders, such as Ti3SiC 2-y N y MAX phase and its etching product two-dimensional Ti3C 2-y N y T x MXene, Ti2AlC 1-y N y MAX phase and its etching products are 2D etched into Ti2C 1-y N y T x MXene, Ti4AlC 3- y N y MAX phase and its etching product two-dimensional Ti4C 3-y N y T x MXene, etc.

Citation Information

Patent Citations

  • Method for preparing two-dimensional nanosheet crystal Ti3C2 alkene

    CN106744961A

  • MXene particle material, slurry, secondary battery, transparent electrode, and method for producing MXene particle material

    CN110892570A

  • MXenes material with controllable terminal group and preparation method

    CN116553549A

  • Preparation of Layered MXene via Elemental Halogen Etching of MAX Phase

    US20210139379A1